Sistem Pendukung Keputusan Penentuan Pelaku Pariwisata Terbaik dimasa Pandemi Covid-19 Menerapkan Metode OCRA dengan Pembobotan ROC (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The Covid-19 pandemic which has an impact on people's lives and tourism management, which results in a decrease in public interest in traveling due to the Covid-19 pandemic which requires all people to comply with the regulations set by the government such as the regulations set, namely keeping a distance from crowds and reducing mobility. . Which is where this regulation can hinder activities in traveling because it is certain that traveling will experience close distances, crowding and leaving the house, then this is the cause of business actors in the tourism sector experiencing a decrease in income. So this study was made to answer the problem of determining the best tourism actors during the COVID-19 pandemic by counting data from 7 alternatives and 7 criteria where the criteria that have been set include the number of visitors / week, the application of the Covid-19 health protocol, time restrictions on visits, the use of vaccine bets. for staff, facilities and infrastructure, cleanliness and sanctions for the covid group, these criteria are calculated using the Rank Order Centroid (ROC) method, where this method can be used to generate a weight of importance for each of the predetermined criteria and the Operational Competiticness Rating method. Analysis which is included in one of the decision support system methods that can produce precise and accurate final preference values. So in the study that was determined as the best tourism practitioner during the COVID-19 pandemic, alternative A3 was the Sidebuk Debuk Berastagi Baths with a final preference value of 1,497 as the best alternative